Meracik Ulang Warisan Rasa: Revitalisasi Gastronomi Bali Kuna melalui Rembuk Rasa Gastronosia - Pambudi, Bondan; Darsana, Made; Wahyu, Gede Eka (Yayasan Literasi Altruis Khatulistiwa, 2025)
Ancient Balinese gastronomy as part of the Intangible Cultural Heritage stores the historical value, spirituality, and philosophy of life of the Balinese people that have not been fully documented. The lack of empowerment and the study and understanding of the younger generation as well as the threat of modernization drives the need for research-based preservation and community participation. This service activity aims to revive the ancient Balinese gastronomic narrative through an interdisciplinary approach in the 2nd Rembuk Rasa Program implemented by the Indonesian Gastronomy Community (IGC). Implementation methods include the study of culinary history literature, focus group discussions, exhibitions, and reconstruction of traditional culinary. The results of the activities show that many elements of ancient Balinese gastronomy still survive but undergo modifications. The culinary narrative was successfully revisited, including cooking techniques, endangered local ingredients, and symbolic value in ceremonial dishes. This activity strengthens cultural awareness and encourages cross-sector collaboration in efforts to conserve traditional Balinese gastronomy.